Answer:
x = 9 and y = 12
Explanation:
-5x + 4y = 3
x = 2y - 15
We solve equation by using elimination method.
-5x + 4y = 3
x = 2y - 15
Solve for y.
Consider the second equation. Subtract 2y from both sides.
In order to solve by elimination, coefficients of one of the variables must be the same in both equations so that the variable will cancel out when one equation is subtracted from the other.
- -5x + 4y = 3, x - 2y = -15
To make -5x and x equal, multiply all terms on each side of the first equation by 1 and all terms on each side of the second by -5.
Simplify.
- -5x + 4y = 3, -5x + 10y = 75
Subtract -5x + 10y = 75 from -5x + 4y = 3 by subtracting like terms on each side of the equal sign.
- -5x + 5x + 4y - 10y = 3 - 75
Add -5x to 5x. Terms -5x and 5x cancel out, leaving an equation with only one variable that can be solved.
combine like terms
Divide both side by -6
Solve for x.
Plug 12 as y in first equation. Because the resulting equation contains only one variable, you can solve for x directly.
Multiply 4 × 12 to get 48.
Subtract 48 from both sides.
- -5x + 48 - 48 = 3 - 48
- -5x = -45
Divide both sides of equation by -5
The system is now solved.
x = 9 and y = 12